Menggagas Konsep Dekriminalisasi Pencemaran Nama Baik Sebagai Pelanggaran Hukum Perdata Murni - Sheila Maulida Fitri (Lex Renaissance, 2020)
Law always comes late as opposed to the social deveopment, existing laws are sometimes no longer able to provide solutions to social problems that occur. It is the same with defamation offenses that are blooming in Indonesia. Settlement of cases through criminal law is considered ineffective to resolve the existing problems. This study aims to identify the problem of law enforcement on defamation offenses in Indonesia and providing the right arguments on the urgency of decriminalizing defamation offenses and altering them onto violations of civil law instead. The research method used is a normative juridical with statutory,analytical approach and comparative approaches. The results of the study conclude that law enforcement on defamation offenses using criminal law efforts is considered ineffective because of problems in the material and formal legal aspects of the related article. The imposition of sanctions in the form of corporal punishment actually creates a new social problem and often does not fulfill the sense of justice for both the perpetrator and the victim, especially if the perpetrator's actions cause material losses. Hence the settlement through civil law is considered very appropriate considering that the majority of defamation occurs between individuals. This is also in order to re-establish the existence of criminal law as the ultimum remedium